PENINGKATAN PENGETAHUAN DAN SIKAP PENGGUNAAN APD PADA PETUGAS POSYANDU DI DESA FANCAWATI, KECAMATAN KLARI, KABUPATEN KARAWANG - Darmawan, Wendi; Yuliana, Chaerani Tri; Jumaedi, Jumaedi; Muhidin, Muhidin; Widhiantika, Wieke (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
The use of Personal Protective Equipment (PPE) is a crucial measure in protecting healthcare workers from the risk of infection exposure in the workplace. However, in Fancawati Village, Klari Sub-district, Karawang Regency, the level of PPE usage among community health volunteers (posyandu staff) remains suboptimal. This community service program aims to enhance knowledge, attitudes, and adherence to PPE usage among posyandu staff through educational activities, training, simulations, and intensive mentoring over one month. The methods used include an initial survey, socialization, training, simulations, mentoring, and evaluation. The results showed an increase in knowledge from 55% to 90%, a positive attitude shift from 50% to 80%, and improved adherence to PPE use from 60% to 85%. Additionally, the number of posyandu units providing PPE independently increased from 3 to 6. This program successfully improved the quality of services at posyandu by raising awareness and better PPE usage behaviors. The success of this program highlights the importance of a holistic approach that involves education, policy support, and adequate facility provision to improve safety standards in primary healthcare facilities